Rice bran: A rice milling byproduct for the production of bioactive compounds and nutraceuticals - Fabian, Cynthia B. (Animo Repository, 2012)
Most of the 677 million tons of rice produced worldwide is milled before consumption. During milling, white rice is produced together with the byproducts, rice hull and rice bran. The rice bran fraction obtained has been reported to be rich in bioactive compounds and potential nutraceuticals such as antioxidants (oryzanols, tocopherols and tocotrienols), proteins and starch. However, utilization of rice bran as a nutritional food is very less. In most countries, nobody used it for food due to its high fiber content and rapid development of rancidity. Generally, it is only used to feed the animals and as a consequence, most people think it is only suited for animal consumption. Extraction of these bioactive compounds and nutraceuticals from rice bran is necessary so that these bioactive compounds and nutraceuticals can be added into functional foods or a new product suitable for human consumption can be produced. Studies have been conducted on rice bran as a source of antioxidants, protein isolates and other bioactive compounds. Some studies produced extracts that contain a mixture of rice bran's bioactive components and were found to have antioxidative, anti-tumor, and cholesterol-lowering activities. Extraction methods of these rice bran components employed the use of solvents, enzymes, subcritical and supercritical conditions. In this chapter, rice bran components and the ways for extracting these components are discussed. This chapter provides recent advances in the extraction methods utilized for the production of new value-added product from rice bran. © 2012 by Nova Science Publishers, Inc. All rights reserved.